From a Pinch to an Open Hand: Appeals to the Evolution of Cooperation in Contemporary Political Thought - Hordern, Joshua (Studies in Christian ethics, 2013)
This article considers the political significance of game theoretical notions of cooperation by responding theologically to the writings of David Willetts, a minister in the UK government. The argument is that the forms of cooperative institutional life which societies require can be neither explained nor planned for solely by mathematical modelling of rational self-interest. What altruistic, civic cooperation depends upon is a complex web of affective trust, often theologically formed by open-handed faith rather than a self-protective pinch, so that wise risks may be taken for the sake of future generations.